2022
DOI: 10.3390/foods11030366
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of the Volatomic Fingerprint of Saffron from Campania towards Its Authenticity and Quality

Abstract: The volatile profiles of eight saffron samples (seven cultivated and one spontaneous) grown in different geographical districts within the Campania region (southern Italy) were compared. Using headspace solid-phase microextraction coupled to gas chromatography–mass spectrometry (HS-SPME/GC-MS), overall, 80 volatiles were identified in the eight landraces. Among them, safranal and its isomers and other related compounds such as isophorones, which are not only key odorants but also pharmacologically active metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Most of identified VOC have been previously reported in saffron from diverse geographical origins by different extraction and detection methods 13,15,19,20,23,24,27,48–51 . The terpenes were the most abundant in all samples, with monoterpenic ketones (such as β‐isophorone, α‐isophorone, and 4‐ketoisophorone) and monoterpenic aldehydes (such as Safranal) being the most represented groups which are line with reported data 19,52 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Most of identified VOC have been previously reported in saffron from diverse geographical origins by different extraction and detection methods 13,15,19,20,23,24,27,48–51 . The terpenes were the most abundant in all samples, with monoterpenic ketones (such as β‐isophorone, α‐isophorone, and 4‐ketoisophorone) and monoterpenic aldehydes (such as Safranal) being the most represented groups which are line with reported data 19,52 …”
Section: Resultssupporting
confidence: 86%
“…and monoterpenic aldehydes (such as Safranal) being the most represented groups which are line with reported data. 19,52 Safranal is the most volatile component of saffron and constitutes about 60% of the volatile fraction. 38 It is the most influential aroma compound that contributes to the overall aroma of C. sativus.…”
Section: Determination Of Volatile Components By Gc-msmentioning
confidence: 99%
“…The results showed that S1 and SE samples contain several volatile compounds, which are naturally present in saffron. The terpenes were the most abundant in both samples, with monoterpenic aldehydes (such as Safranal ) and monoterpenic ketones (such as isophorone, and 4-ketoisophorone) being the most represented groups, which are in line with reported data [8,54]. This finding confirmed our results obtained by FTIR and barcoding techniques.…”
Section: Gaz Chromatography -Mass Spectrometrysupporting
confidence: 92%
“…The VOMs identified only in saffron are listed in Table S1 . Cozzolino et al [ 27 ] conducted a comprehensive evaluation of the volatomic fingerprint of saffron with the aim of testing its authenticity and quality. Many of the VOMs identified in our samples agrees with the data provided in that work.…”
Section: Resultsmentioning
confidence: 99%